2020
DOI: 10.1111/myc.13136
|View full text |Cite
|
Sign up to set email alerts
|

Visualising virulence factors: Trichophyton benhamiaes subtilisins demonstrated in a guinea pig skin ex vivo model

Abstract: Background Dermatophytoses rank among the most frequent communicable diseases in humans, and the zoonotic transmission is increasing. The zoophilic dermatophyte Trichophyton (T.) benhamiae is nowadays one of the main causes of tinea faciei et corporis in children. However, scientific data on molecular pathomechanisms and specific virulence factors enabling this ubiquitous occurrence are scarce. Objectives To study tissue invasion and the expression of important virulence factors of T. benhamiae, isolates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
(73 reference statements)
1
7
1
Order By: Relevance
“…Here, furthermore, each species forms its own subclade; this is also seen in the MALDI-TOF MS dendrogram apart from T. verrucosum with one isolate clustering together with the veterinary T. erinacei-isolates. However, the nested arrangement of T. erinacei, T. verrucosum and T. benhamiae together in one subcluster in the MSP-dendrogram underlines their close interspecies-relation which is not only seen in other proteome analyses (Bartosch et al, 2018) but also reported in other genomic studies (Gräser et al, 2008;Baumbach et al, 2020). Furthermore, the latter is also supported by the current ITS-tree in which these three species form one common subclade as well.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Here, furthermore, each species forms its own subclade; this is also seen in the MALDI-TOF MS dendrogram apart from T. verrucosum with one isolate clustering together with the veterinary T. erinacei-isolates. However, the nested arrangement of T. erinacei, T. verrucosum and T. benhamiae together in one subcluster in the MSP-dendrogram underlines their close interspecies-relation which is not only seen in other proteome analyses (Bartosch et al, 2018) but also reported in other genomic studies (Gräser et al, 2008;Baumbach et al, 2020). Furthermore, the latter is also supported by the current ITS-tree in which these three species form one common subclade as well.…”
Section: Discussionsupporting
confidence: 77%
“…Also, A. insingulare and A. crocatum show this separation according to the origin of isolation. This phenomenon is not observed in the current ITS-dendrogram and was also not seen in a previous study with T. benhamiae-isolates derived from human patients and infected guinea pigs (Baumbach et al, 2020). However, for T. erinacei this may be explained with the different geographical sampling sites of these isolates (human: Central Germany; hedgehog: Hannover area).…”
Section: Discussioncontrasting
confidence: 60%
“…Nevertheless, after incubation on PDA at 30 • C under 12% CO 2 , identified as the optimal culture condition for viable fungal concentration, dermatophytes produce arthroconidia with percentages ranging from 1% to 68% for T. rubrum IHEM 13894 or 82% for M. canis IHEM 21239. The spore suspensions produced in these conditions are therefore "enriched in arthroconidia" compared to suspensions exclusively composed of microconidia and previously used as inoculum in many models [17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental infection models described in the literature use different compositions of inoculum, consisting in suspensions enriched in unicellular infective spores, namely microconidia [17][18][19][20][21][22][23] or arthroconidia [24][25][26][27][28][29], or in a mix of microconidia and hyphae [30][31][32][33][34][35]. Microconidia, as well as macroconidia, are a type of thallic spores resulting from lateral or terminal budding of hyphae.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, standardized inocula of the dermatophytes' conidia were applied to GPSE in a transwell cell culture system. Adhesion, invasion and infection of the skin explants by fungal elements were monitored for up to ten days and the important virulence factors subtilisin (Sub) 3 and 6 as well as metallocarboxypeptidase A (MCPA) were assessed at protein level using immunofluorescence (IF) analyses [10].…”
Section: Introductionmentioning
confidence: 99%